2011
DOI: 10.1108/08288661111181305
|View full text |Cite
|
Sign up to set email alerts
|

WAQF accounting and management in Indonesian WAQF institutions

Abstract: PurposeThe purpose of this study is to examine accounting and management practices in two Indonesian awqaf institutions. It intends to seek evidence with regard to how mutawallis discharge their accountability.Design/methodology/approachTwo case studies were undertaken on two awqaf institutions in Indonesia, i.e. ABC and XYZ waqf foundations. Data were collected through various methods, i.e. interviews, document reviews and direct observations.FindingsThe findings show that ABC shows more efficient management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 4 publications
2
70
2
4
Order By: Relevance
“…al. 1999;Siti Rokyah 2005;Hisham 2006;Ihsan 2007;Mohd Nasir 2009;Ihsan & Adnan 2009;Ihsan & Ibrahim 2011;Daud et. al.…”
Section: The Need For Standardisation Of Waqf Accounting and Reportingunclassified
See 2 more Smart Citations
“…al. 1999;Siti Rokyah 2005;Hisham 2006;Ihsan 2007;Mohd Nasir 2009;Ihsan & Adnan 2009;Ihsan & Ibrahim 2011;Daud et. al.…”
Section: The Need For Standardisation Of Waqf Accounting and Reportingunclassified
“…This means at the end of year, the waqf assets and revenues, liabilities and expenses related to waqf are added to the account of the SIRCs. Prior study indicate that majority of SIRC did not separate its waqf account (Ihsan & Ibrahim 2011). Whereas, few SIRCs or waqf units has its own financial reporting specifically for waqf which are later consolidated in the SIRCs reporting which is known as Kumpulan Wang Wakaf like SIRC of Selangor, Johor, Wilayah Persekutuan and Negeri Sembilan.…”
Section: Measurement or Valuation Of Waqf Assetmentioning
confidence: 99%
See 1 more Smart Citation
“…Ihsan and Mohamed Ibrahim (2011) believe that waqf institutions should be more transparent in their financial reporting practices. The authors found that between the two Indonesian waqf institutions that they observed, the waqf institution that is more transparent (i.e., discloses its financial reports to the public) represents better accountability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that it was extremely popular in Anatolia and the European provinces of the Empire (Toraman et al 2007). Previous studies also showed that cash waqf had played a major role in helping disadvantaged Muslim societies managing their social and socio-economic conditions (Toraman et al 2007;Harun et al 2012;Kahf 1992;Ihsan 2011;Kahf 1999) Yet, the credibility of waqf institutions are being debated by many parties due to poor management and administration of waqf properties (Ihsan 2011). A survey conducted in Jakarta and West Java, Indonesia found that most people did not have much trust in their existing public waqf institutions.…”
Section: Introductionmentioning
confidence: 99%